2013
DOI: 10.4209/aaqr.2012.03.0054
|View full text |Cite
|
Sign up to set email alerts
|

Composition and Mass Closure of PM2.5 in Urban Environment (Athens, Greece)

Abstract: Daily PM 2.5 concentrations and composition were monitored at an urban site at 14 m above ground level, at the National

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
28
2
17

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 31 publications
11
28
2
17
Order By: Relevance
“…Also, the highest fluctuations were observed at THR station most probably because of the distance of the station from anthropogenic emissions (Grivas et al, 2004), whereas the lowest were found at ARI, PIR-1 and GOU stations due to their proximity to traffic and other urban sources of PM 10 emissions. It is also observed in Figs (Remoundaki et al, 2013). However, some of the annual peaks observed in PM 10 concentrations were attributed to forest fires (ARI 2007, PIR-1 2006, LYK 2001, GOU 2007 or other sources mainly at the traffic urban areas (most probably anthropogenic pollution; ARI 2001-2002, MAR 2001-2003, PIR-1 2007, AGP 2001, GOU 2006.…”
Section: Contribution From African Dust Load To the Pm 10 Concentrationsmentioning
confidence: 74%
See 1 more Smart Citation
“…Also, the highest fluctuations were observed at THR station most probably because of the distance of the station from anthropogenic emissions (Grivas et al, 2004), whereas the lowest were found at ARI, PIR-1 and GOU stations due to their proximity to traffic and other urban sources of PM 10 emissions. It is also observed in Figs (Remoundaki et al, 2013). However, some of the annual peaks observed in PM 10 concentrations were attributed to forest fires (ARI 2007, PIR-1 2006, LYK 2001, GOU 2007 or other sources mainly at the traffic urban areas (most probably anthropogenic pollution; ARI 2001-2002, MAR 2001-2003, PIR-1 2007, AGP 2001, GOU 2006.…”
Section: Contribution From African Dust Load To the Pm 10 Concentrationsmentioning
confidence: 74%
“…In particular, Papayannis et al (2008) found that the seasonal pattern of dust transport toward Europe is enhanced in the central and eastern Mediterranean during spring whereas Kallos et al (1998) and Rodriguez et al (2001) have shown that intrusions of Sahara dust in the region mainly occur during the winter and spring. Additionally, Remoundaki et al (2013) examined the PM 2.5 concentrations over Athens during 2010 and found the maximum, and with the most frequent abrupt changes, concentrations of elements which are typical constituents of dust (Si, Al, Ca, Fe, K, Mg, Ti) during spring and autumn. Extreme Sahara outbreaks occurred also during winter however their effect on PM 10 concentrations in AMA is for approximately 53% of the events less than 19 μg/m 3 .…”
Section: Contribution From African Dust Load To the Pm 10 Concentrationsmentioning
confidence: 99%
“…A description of the Athens Basin and prevailing meteorological conditions has been provided in the literature (Chaloulakou et al, 2005;Grivas et al, 2008Grivas et al, , 2012Kanakidou et al, 2011;Theodosi et al, 2011). Studies performed in the Athens Basin demonstrated the prevailing emissions of carbonaceous aerosol all year round, namely from vehicles, fuel combustion and long-range transport (Chaloulakou et al, 2005;Sillanpaa et al, 2006;Grivas et al, 2012;Pateraki et al, 2012;Remoundaki et al, 2013). Nevertheless, it is essential to note that there are limited studies concerning the PM 2.5 fraction of aerosol in Athens, and the studies performed so far have been conducted for short time periods (4-11 months), mainly at urban locations.…”
Section: Paraskevopoulou Et Al: Long-term Characterization Of Orgmentioning
confidence: 99%
“…Turpin and Lim (2001) Pateraki et al (2012) 12 Terzi et al (2010) 13 Bougiatioti et al (2013) 14 Koulouri et al (2008) 15 16 Kopanakis et al (2012) 17 Piazzola et al (2012) 18 Pey et al (2009a) 19 Pey et al (2009b) suggest the use of different conversion factors according to site type: 1.6 ± 0.2 for urban areas, 1.9-2.3 for aged aerosols and 2.2-2.6 for biomass burning. Taking into account that our site is an urban background station which is also affected by long-range transport (e.g., Sciare et al, 2005;Kanakidou et al, 2011;Pateraki et al, 2012;Remoundaki et al, 2013), we used the value of 2.1 (OM = 2.1 · OC). On average, OM accounts for 24 ± 6 % of PM 2.5 , which is consistent with the value (22 %) provided by Remoundaki et al (2013) for Athens, while it is lower than those reported at other European sites (e.g., Sillanpaa et al, 2005;Sanchez de la Campa et al, 2009).…”
Section: Mass Concentrations Of Oc-ec and Observed Seasonal Trendsmentioning
confidence: 99%
See 1 more Smart Citation